HIGH RIGIDITY AND VIBRATION ENDURANCE BAR FOR DEEP HOLES (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
Different constructions of bars are analyzed in the article, all of which are based on the idea of creating prestressed state in material. Improved construction of bar is proposed for equable spreading of elasticity zone along axis of boring bar.